International versus domestic shocks and pass-through to country prices: A heterogeneous VAR approach - Vanessa Alviarez; Peter Louis Pedroni; Andrew Powell; Ingri Quevedo (Inter-American Development Bank (IDB), 2025)
This study investigates the disconnect between falling agricultural commodity prices and persistent food inflation by applying a Heterogeneous Vector Autoregression (VAR) model to a panel of 203 countries using data from 1961 to 2022. It analyzes the impact of global crops, fertilizer, and oil prices on domestic inflation and explores the asymmetries in the pass-through of global shocks. Results show that fertilizer price shocks significantly influence crop prices, especially maize and soybeans, while production shocks have a weaker effect. Demand-driven price changes exhibit higher pass-through to food inflation compared to supply-driven shocks, with country-specific characteristics shaping these responses. A historical decomposition reveals that global factors played a larger role in inflation during 2021, particularly for emerging economies, while advanced economies were more affected by domestic shocks. These findings highlight the importance of tailored policies to mitigate inflation in the face of global commodity price volatility.
Keywords: E30; E31; Q02; Q11; 330; Food prices; Commodities; Inflation; Agriculture